Microbial Communities of the Shallow-Water Hydrothermal Vent Near Naples, Italy, and Chemosynthetic Symbionts Associated With a Free-Living Marine Nematode - Bellec, Laure; Cambon-Bonavita, Marie-Anne; Durand, Lucile; Aube, Johanne; Gayet, Nicolas; Sandulli, Roberto; Brandily, Christophe; Zeppilli, Daniela (Frontiers in Microbiology, 2020)
Shallow-water hydrothermal vents are widespread, especially in the Mediterranean Sea, owing to the active volcanism of the area. Apart free microbial communities’ investigations, few biological studies have been leaded yet. Investigations of microbial communities associated with Nematoda, an ecologically important group in sediments, can help to improve our overall understanding of these ecosystems. We used a multidisciplinary-approach, based on microscopic observations (scanning electron microscopy: SEM and Fluorescence In Situ Hybridization: FISH) coupled with a molecular diversity analysis using metabarcoding, based on the 16S rRNA gene (V3-V4 region), to characterize the bacterial community of a free-living marine nematode and its environment, the shallow hydrothermal vent near Naples (Italy). Observations of living bacteria in the intestine (FISH), molecular and phylogenetic analyses showed that this species of nematode harbours its own bacterial community, distinct from the surrounding sediment and water. Metabarcoding results revealed the specific microbiomes of the sediment from three sites of this hydrothermal area to be composed mainly of sulfur-oxidizing and reducing related bacteria.